Legal Interpretation of Regulation Law No. 2 of 2012 Concerning Land Acquisition for Development in The Public Interest - Nurnaningsih Nurnaningsih (Veteran Law Review, 2023)
Law No. 2 of 2012 concerning Land Acquisition for Development in the Public Interest (Land Acquisition Law) has been a guideline for the government in conducting land acquisition for more or less 10 years. In the Land Acquisition Law, land allotment for development in the public interest does not include mining as a part of development in the public interest This research aims to analyze and understand the Legal Interpretation of Regulation Law No. 2 of 2012 Concerning Land Acquisition for Development in The Public Interest. The method of this research is library research as a research in literature or an activity to compile information relevant to topic or object of research and received from books, scientific paper, thesis, dissertation, encyclopedia, internet and other resources. The research shows the result is To ensure the availability of land for public interest by taking into account the balance between the interests of development and the interests of the community.